2019
DOI: 10.1080/15384101.2019.1648959
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulated lncRNA UCA1 acts as ceRNA to adsorb microRNA-498 to repress proliferation, invasion and epithelial mesenchymal transition of esophageal cancer cells by decreasing ZEB2 expression

Abstract: Objective: Esophageal cancer (EC) is one of the most general malignant tumors in humans. There were few studies researching the connections between lncRNA UCA1 and EC. This study is to research the effect of lncRNA UCA1 adsorbing microRNA-498 (miR-498) as a ceRNA to regulate ZEB2 expression on epithelial mesenchymal transition (EMT), invasion and migration of EC cells. Methods: UCA1, miR-498 and ZEB2 expression in EC tissues and cells was detected by RT-qPCR or western blot analysis. EC cells were transfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…[14][15][16][17] It has been reported that UCA1 contributes to the progression of prostate cancer by regulating proliferation and metastasis through inactivation of KLF4-KRT6/13 signaling pathway, 18 and functioning as a sponge for miR-184, 19 miR-204, 20 or miR-498. 21 Moreover, UCA1 promotes progression of colon cancer 22 and osteosarcoma, 23 and correlates with poor prognosis of ovarian cancer patients. 24 UCA1 can be induced by TGF-β1 25 and its upregulation leads to enhanced invasion and migration in gastric cancer cells.…”
mentioning
confidence: 99%
“…[14][15][16][17] It has been reported that UCA1 contributes to the progression of prostate cancer by regulating proliferation and metastasis through inactivation of KLF4-KRT6/13 signaling pathway, 18 and functioning as a sponge for miR-184, 19 miR-204, 20 or miR-498. 21 Moreover, UCA1 promotes progression of colon cancer 22 and osteosarcoma, 23 and correlates with poor prognosis of ovarian cancer patients. 24 UCA1 can be induced by TGF-β1 25 and its upregulation leads to enhanced invasion and migration in gastric cancer cells.…”
mentioning
confidence: 99%
“…In renal cancer, UCA1 plays a critical regulatory role in proliferation and progression of renal cancer cells by interacting with miR-182-5p/DLL4 axis [21]. In gastric cancer, UCA1 works with miR-7, 495, 498 to promote tumor-genesis [22,23]. In MNK45 gastric cancer cell line, we demonstrated that UCA1 sponges miR-204 to free its target gene ZEB1 (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have suggested that miR-498 level was lower in EC tissues/cells than in normal tissues/cells. 33 Here, we detected the level of miR-498 in EC cells. In agreement with the previous data, our results confirmed that miR-498 expression was downregulated in EC cells.…”
Section: Discussionmentioning
confidence: 93%